Methods for Incorporating Stakeholder Engagement into Clinical Trial Design. Issue 1 (10th May 2017) - Ehlers, Anne P.; Davidson, Giana H.; Deeney, Kimberly; Talan, David A.; Flum, David R.; Lavallee, Danielle C.
Context: Lack of engagement with healthcare stakeholders results in missed opportunities to understand translation of evidence into practice. Case: Stakeholder engagement is a key component of the Comparing Outcomes of Drugs and Appendectomy (CODA) Study, a pragmatic clinical trial funded by PCORI to evaluate the effectiveness of antibiotics versus urgent appendectomy for acute uncomplicated appendicitis. We provide a framework for developing a stakeholder coordinating center (SCC) and describe two examples of how stakeholder engagement can inform study development. Findings: Coordinating engagement activities through the SCC established a commitment to the important partnership with stakeholders. It also facilitated communication and provided a central mechanism for obtaining input on key decisions such as development of patient-centered consent documents and appropriate stopping rules for a specific sub-population of patients with appendicitis. Major themes: Translatable lessons include thoughtful planning for engagement, identifying stakeholders with a direct interest in the study conduct and findings, and integration of input received into the decisions that drive the conduct of the study. Conclusions: Standards for conducting patient-centered research should address the ability to successfully engage patients by demonstrating the capacity to recruit study participants, engage them over the duration of the study, and disseminate findings that are congruent with stakeholder needs. The process of sharing important clinical research findings has improved patient care, and we believe that dissemination of novel engagement strategies can lead to increased success in study design and execution.